Pengaruh Brand Awareness dan Brand Image serta Word Of Mouth terhadap Brand Trust dan Pembentukan Brand Loyalty pada Pelanggan Cbezt Friedchiken Kecamatan Genteng Banyuwangi - Asri Oktiani; Rozy Khadafi (COSTING : Journal of Economic, Business and Accounting, 2018)
Cbezt friedchiken implements marketing strategies that match the products produced with the goal of growing brand loyalty so that longterm is expected to add loyal customers as well as revenue. This study aims to determine the effect of brand awareness, brand image and world of mouth to brand trust and brand loyalty to Cbezt fried Chiken customers. sub district Genteng Banyuwangi. The research method used is explanatory research, analysis tool used path analysis with sample 50 respondents. The results of the analysis obtained the answer that the independent variables that have the strongest influence on brand loyalty variables through variable intervening brand trust is variable word of mouth. Keywords: brand awareness, brand image, word of mounth, brand trust, brand loyalty